2021
DOI: 10.3390/antiox10060915
|View full text |Cite
|
Sign up to set email alerts
|

‘Carbon-Monoxide-Releasing Molecule-2 (CORM-2)’ Is a Misnomer: Ruthenium Toxicity, Not CO Release, Accounts for Its Antimicrobial Effects

Abstract: Carbon monoxide (CO)-releasing molecules (CORMs) are used to deliver CO, a biological ‘gasotransmitter’, in biological chemistry and biomedicine. CORMs kill bacteria in culture and in animal models, but are reportedly benign towards mammalian cells. CORM-2 (tricarbonyldichlororuthenium(II) dimer, Ru2Cl4(CO)6), the first widely used and commercially available CORM, displays numerous pharmacological, biochemical and microbiological activities, generally attributed to CO release. Here, we investigate the basis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 71 publications
(102 reference statements)
0
36
0
Order By: Relevance
“…It was found that the ruthenium-based CORM-2 and CORM-3 mainly liberate CO 2 (besides only little CO), confirming the results of Poole and co-workers that the use of these first-generation CORMs as reference CORMs may no longer be appropriate. [12] Noteworthy, no CO 2 was released from the iron-based AT-and ET-CORMs after enzymatic hydrolysis. Based on the aforementioned observation that extraand intra-cellular CO delivery yield similar anti-inflammatory properties, our study suggests that the use of specific membrane associated enzymatic activity may pave the way for tissue-targeted CO delivery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that the ruthenium-based CORM-2 and CORM-3 mainly liberate CO 2 (besides only little CO), confirming the results of Poole and co-workers that the use of these first-generation CORMs as reference CORMs may no longer be appropriate. [12] Noteworthy, no CO 2 was released from the iron-based AT-and ET-CORMs after enzymatic hydrolysis. Based on the aforementioned observation that extraand intra-cellular CO delivery yield similar anti-inflammatory properties, our study suggests that the use of specific membrane associated enzymatic activity may pave the way for tissue-targeted CO delivery.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Also, Poole and co-workers have recently shown that CORM-2 only releases negligible amounts of CO (< 0.1 mol CO per mol CORM-2) and concluded that the biological effects of CORM-2 and related CORMs should be re-examined in the light of these data. [12]…”
Section: Co-releasing Propertiesmentioning
confidence: 99%
“…5 ). Southam, M. et al also showed that CO derived from the CORM-2 was nearly exhausted after a 4 h period of incubation in DMSO [ 67 ]. We further confirmed that the treatment of HK-2 cells with iCORM-2 did not activate HIF-1α, AMPK, and Nrf-2, all of which were activated by the CORM-2 treatment (S. Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is still not clear how Ru complexes enter cells, though one possibility is that they use iron transport mechanisms [ 14 ]. Once inside cells, ruthenium is able to bind to proteins (via cysteine thiols [ 16 , 17 ] or histidines [ 18 ]), to free thiols such as glutathione [ 16 , 17 ], and also to DNA. In this behaviour it shows interesting differences as compared with platinum, which binds mainly to DNA, and tends to form square planar complexes, in particular linking the N7 positions of adjacent guanines, while ruthenium forms octahedral complexes [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that CORM-3 is toxic to bacterial cells but shows little toxicity to mammalian cells, which has stimulated research on modes of action of the Ru-based CORMs that have focussed on the toxicity of CO. However, recently we showed that CORM-3, as well as the related molecule CORM-2, in fact release very little CO in standard growth conditions [ 16 , 17 , 22 ]. Furthermore, we showed that the bacterial toxicity is due to the ruthenium(II) ion and probably not to CO at all.…”
Section: Introductionmentioning
confidence: 99%